P87 MEDIASTINAL SYNDROME REVEALED HEART LOCALIZATION OF A PRIMARY MEDIASTINAL B–CELL LYMPHOMA. (18th May 2022) - Branca, E; Cicco, S; Susca, N; Longo, L; Albanese, F; Pappagallo, F; Giliberti, T; Morelli, C; Dell'Atti, C; Ingravallo, G; Prete, M; Solimando, A; et al.
Abstract: Background: Primary mediastinal B–cell lymphoma (PMBCL) is an aggressive B–cell lymphoma that represents 2–3% of non –Hodgkin lymphoma cases and typically affects young adult Caucasian women. Diagnosis can be difficult and often need a multidisciplinary approach. Case: a 75 year old female, with history of hypertension, came to ER for severe dyspnea. She complains also neck and left arm oedema. Blue swelling of face and trunk were described. Heart PoCUS was inconclusive, describing only a hypoechoic dilation of right atrium while the other three heart chambers were reduced in dimensions. Chest TC revealed a huge mediastinal mass next to a thrombosis of superior cava vein and right atrium (7 cm diameter) and a diffuse subsegmental pulmonary embolism. Arm and neck Lymphnodes were also enlarged . Low molecular weight heparin was given twice a day. Due the respiratory failure a high–flow nasal cannula oxygen treatment was performed. PET revealed FDG uptake in antero–superior mediastinum, but there was the same uptake in heart right atrium without a connection with the previous described. Therefore, this was no more considered as thrombus but as mass. The micro–bubble test revealed right to left shunt. She refused heart MRI. The patient was not suitable for an open–surgery biopsy, thus she was scheduled for a TC guided one, in order to obtain a pathological diagnosis for a suspected right atrium sarcoma. Due to the high risk we choose to perform the less invasive as possible way to have a histological sample. Thus, and intravascular biopsy of atrial mass by femoral vein was performed. The patient did not present any sequelae after procedure and she continued anticoagulation. The subsequent histological analysis revealed a PMBCL with a primary localization in Right atrium. Unfortunately, a sepsis by multiple resistant pseudomonas Aeruginosa and Aspergillus spp. arose and the patient died three weeks after biopsy. Conclusion: A PMBCL is a rare and aggressive disease. Like in our patient, mediastinal syndrome is often associated to the disease. However, intracardiac localization are even rarer events. In large case series, less than 1% of intracardiac masses were lymphomas. In our patient, open–surgery was not suitable for multiple comorbidities. However, intravascular approach was less aggressive but effective to obtain enough tissue for diagnosis. Unfortunately, the immune suppression related to PMBCL and opportunistic infections drive a mortal sepsis.